The economic effects of tax incentives on the mutual fund industry in Barbados - Alleyne, Kerry-Ann (2006)
Examines the effects of tax incentives on portfolio composition, by producing an assessment of the 1996 Amendment to the Barbados Income Tax Act on the demand for mutual funds. Focuses on whether the amendment altered the demand for mutual funds and as well, whether the shift in demand for mutual funds impacted on other categories of the consumer's asset portfolios.